Nanotubular Geometry for Stabilizing Metastable 1T‐Phase Ru Dichalcogenides. Issue 3 (27th November 2022) - Kim, Myeong‐Geun; Kim, Seung‐Hoon; Jang, Jue‐Hyuk; Lee, Dong Wook; Choi, Daeil; Park, Jae‐Hyun; Lee, Kug‐Seung; Chen, Nanjun; Hu, Chuan; Lee, Young Moo; Yoo, Sung Jong
Abstract: Owing to their remarkable electrochemical activities, 1T phase transition metal dichalcogenide (TMD) materials have attracted considerable interest in recent decades. However, metastable 1T phases are difficult to prepare and readily change phases. Therefore, for the first time, a monolayer nanotubular 1T Ru dichalcogenide comprising 92% of the 1T phase is synthesized, which is the highest value ever obtained using solvothermal methods. In the tubular geometry, the 1T phase exhibits superior durability against various external stimuli and electrocatalytic activity toward the oxygen reduction reaction. According to density‐functional‐theory‐based and molecular dynamics calculations, sufficiently curved architectures can change their bond identities to safely maintain 1T phases, hence providing a strategy for stabilizing metastable phases. The study results form a basis for extensively applying 1T phases and will stimulate interest for applying tubular structures for stabilizing metastable materials. Abstract : Development of a strategy for stabilizing 1T materials is highly desirable, since the poor phase stability has hindered its widespread applications. The nanotubular system stabilizes the phase by changing the original bond identities. With a high 1T‐to‐2H‐phase ratio (92%), Ru dichalcogenide nanotubes effectively catalyze the oxygen reduction reaction [half‐wave‐potential ( E 1/2 ) = 0.864 eV, and maximum‐power‐density ( W max ) = 0.526 W cm −2 ].